Peran Lembaga Pusat Pelaporan dan Analisis Dalam Penaggulangan Tindak Pidana Money Laundring - I Wayan Panca Eka Darma; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Kertha Wicaksana, 2020)
This study aims to determine the role of the PPATK in handling money laundering after the enactment of Law No. 8 of 2010 concerning the prevention and eradication of money laundering and how criminal sanctions against money laundering in Indonesia. This study uses a normative legal method with a statutory approach. The conclusion of this research is first, PPATK as an independent institution that has 3 (three) main roles in the prevention and eradication of money laundering by receiving reports on suspicious financial transactions, analyzing reports received from the reporting party and then forwarding the results of the report analysis to the parties authorized. Where in the functions and duties of the PPATK are regulated in articles 30 through article 44 of Law No. 8 of 2010 concerning Prevention and Eradication of Money Laundering. Secondly, in the verdict Number: 339 / PID.B / 2010 / PN.JKT.PST, the contents of the decision stated that defendants I and II in the primer snare violated article 2 paragraph 1 in conjunction with article 18 of Law Number 31 of 1999 concerning criminal corruption as amended by Law Number 31 of 2001, challenge the amendment to Law Number 31 of 1999 in conjunction with article 55 paragraph 1 of the Criminal Code